2021
DOI: 10.1186/s12957-021-02206-5
|View full text |Cite
|
Sign up to set email alerts
|

An abdominal-sacral approach with preoperative embolisation for vulvar solitary fibrous tumour: a case report

Abstract: Background Solitary fibrous tumours (SFTs) in the female genital tract are uncommon. Resection of these tumours is controversial because it can cause life-threatening haemorrhage. We report a case of vulvar SFT that was excised in a combined abdominal-sacral approach after preoperative embolisation. Case presentation At another hospital, an inoperable intrapelvic tumour was diagnosed in a 34-year-old woman. Computed tomography and magnetic resonanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, repeated surgeries for recurrent SFTs or too-large tumors can cause distressful adhesion, and complete surgical resection is considerably challenging [ 15 ]. To avoid a positive surgical margin and reduce operative blood loss, several studies have reported the utility of preoperative transcatheter arterial embolization, as SFTs are usually hypervascular tumors [ 5 , 25 ]. In our case, the main pelvic tumor had grown so large that the tumor had severe adhesion to the rectum and the left ureter, so it might have been wise to consider preoperative transcatheter arterial embolization followed by surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, repeated surgeries for recurrent SFTs or too-large tumors can cause distressful adhesion, and complete surgical resection is considerably challenging [ 15 ]. To avoid a positive surgical margin and reduce operative blood loss, several studies have reported the utility of preoperative transcatheter arterial embolization, as SFTs are usually hypervascular tumors [ 5 , 25 ]. In our case, the main pelvic tumor had grown so large that the tumor had severe adhesion to the rectum and the left ureter, so it might have been wise to consider preoperative transcatheter arterial embolization followed by surgery.…”
Section: Discussionmentioning
confidence: 99%